Теорія імпульсів в урбаністичному розвитку великого міста - Павлів, Андрій Петрович (Національний університет "Львівська політехніка", 2019)
Дисертацію присвячено явищу імпульсного розвитку містобудівних систем, особливу увагу звернено на специфічні умови сучасної постіндустріальної урбаністики. На прикладі цілої низки міст розглянуто процеси імпульсного творення урбаністичних структур, характерних для різних суспільно-економічних укладів. Проведений аналіз джерельної бази окреслив чотири принципові фактори історичного містобудування, котрі можна розглядати як імпульсні – інфраструктурні, демографічні, економічні, міфотворчі. Визначено перспективні засади моделювання гіперурбанізованих структур, до яких належить формування: життєпростору широкого вибору, стратегію змінної подіє́вості, техно-біосферного симбіозу, регіонального накопичення глобальної присутності. У цьому контексті розглянуто окремі трансформації містобудівної тканини Львова, здійснені у рамках проведення Чемпіонату Європи із футболу 2012 року, які мали характер містотворчого імпульсу; а також наведено прогностичну картину їх подальшого розростання і розвитку. The aim of the work is to study the phenomenon of impulse urban development, with emphasis on the specific conditions of modern post-industrial urbanism. On the example of several cities, impulse-forming processes of urban structures that are characteristic of various socio-economic structures (agricultural, industrial, post-industrial) are considered. The introduction presents the relevance of the research topic, defines the purpose and objectives of the research, subject, methods of research, scientific novelty and practical significance of the results of the study, approbation of the results of work, the number of publications relevant to the research and the structure and scope of work. The work presents systematization of the material and initiates an actual urban development discourse in accordance with the priorities of this research. They can, basically, be divided into three groups: futuristic, which view formation transformation as a hypothesis, the final confirmation of which belongs to the future, but its probability follows from the abstract-logical scheme proposed by the authors; manifestational, which are affirmative and promotional by nature, and are often combined with propagation of certain technological and engineering solutions, most often from the field of communication and energy innovations; and reflexive ones, which are based on a critical analysis of already implemented transformations. It also presents systematization of applied methods for investigating impulse factors, which triggered the development of a city. The work consists of five chapters. The first of these looks at the examples of spin-off urban development in historical retrospective and according to chronological order. The second represents a study of examples of spin-off development of urban fabric in modern (post-industrial) epoch. The third is the development of research techniques that would allow us to visualize the synthesis of general historical patterns of impulse development and those particular notable features that determine urban development of the post-industrial era. The fourth is theoretical generalization and conceptual arrangement of elements of practical experience of the author in the field of modeling of urban structure on the example of Lviv and a set of functional analogies associated with it. The fifth is analysis, systematization and differentiation of materials that make it possible to distinguish between positive and negative examples of the spin-off development of modern post-industrial urban fabric. In this context, there are two important aspects to be mentioned. The range of methods, which were used to obtain the results of work are specified here, namely: comparative analysis, the method of formational selection, structural-performative synthesis, formation-convergent synthesis, stage analysis, etc. The phenomenon of rapid development of urban structure in a short period of time under the influence of certain factors has been considered. Four main universal factors of historical urban development, which can be viewed as impulse-based, with clearly expressed changes - infrastructural, demographic, economic, and myth-making, were substantiated. The inner content of each of these factors has been outlined and illustrated by relevant examples (Stockholm, Athens, Singapore, Jerusalem). In addition to the universal ones, a number of impulse factors that have formational nature and are determined by socially- economic specificity of certain historical epoch has been described. With reference to the range of cities, main features of the impulses in agricultural (Venice), industrial (Chicago), and post-industrial (Shanghai) epoch have been considered. Different factors have been formulated, which worked out to implement those impulses into practical urban development. The phenomenon of poly-impulses, which stems from the uniquely large scale of the hyper-city of the post-industrial era, is considered. Such huge urban structures, imply more detailed analysis of dialectics of existence of many impulses within a single city. The difference between modern poly-impulse concept and the theory of polycentricity, which was characteristic of the modernist era, has been explained. Providing the examples of Great San Francisco and Los Angeles, elements of poly-impulse evolution of urban fabric have been considered. The concept of micro-oikumene, as a structural model of modern urban space, has been described, which allows us to talk about transformation of the administrative structure of a modernist city. Диссертация посвящена феномену импульсного развития градостроительных систем, с акцентом на специфических условиях постиндустриальной урбанистики. На примере целого ряда городов рассмотрены процессы импульсного создания урбанистических структур, характерных для различных общественно-экономических укладов. Проведенный анализ источников обозначил четыре принципиальные факторы исторического градостроительства, которые можно рассматривать как импульсные и имели форму четко выраженных изменений - инфраструктурные, демографические, экономические, мифотворческие. Определены перспективные основы моделирования гиперурбанизированных структур, к которым относится формирования: жизнєпространства широкого выбора, стратегию переменной событийности, техно-биосферного симбиоза, регионального накопления глобального присутствия. В этом контексте, рассмотрены отдельные трансформации градостроительной ткани Львова, произведенные в рамках проведения Чемпионата Европы по футболу 2012 года, которые имели характер градообразующего импульса; а также приведена прогностическую картину их дальнейшего развития.
Impulse-based theory in the concept of urban development of a large city
Теория импульсов в урбанистическом развитии большого города
Keywords: імпульс; місто; постіндустріальність; моделювання; impulse; city; post-industrial; modeling; импульс; город; постиндустриальность; моделирование; 711.4-043.86 (043.3)